Comparison of Physical Fitness and Learning Motivation in Nature School Students and Regular School Students - Dicky Oktora Mudzakir; Riki Ramadhan; Mochamad Zakky Mubarok; Fauzan Effendy; Fitrianisa Setianing Widi (Journal of General Education and Humanities, 2025)
This study aimed to determine whether there were differences in academic achievement, physical fitness, learning motivation, and motor skills between nature school students and regular school students. In this study, the author used ex post facto research with a comparative type, which was intended to find fundamental answers about cause and effect by analyzing the factors that caused the problem. This study's population were students from nature schools in Bandung and students from Sukajadi 9 Elementary School in Bandung. In this study, the researcher used purposive sampling to take samples with certain criteria and considerations, namely class VI, which had 15 people from nature schools, and class VI, which had 15 students from regular schools. The results of this study used hypothesis testing calculations using the t-test with one shoot design. Based on the hypothesis test results, there were significant differences between academic achievement, physical fitness, learning motivation, and motor skills in nature schools and regular schools.